The influence of IGF-I and Emdogain on the behavior of dental epithelial cells in a three-dimensional scaffold model - Maria Johanna Jacoba Heezen; Weibo Zhang; Sara Rudolph; X. Frank Walboomers; Pamela C. Yelick (University Library System, University of Pittsburgh, 2022)
Aim: Tooth decay and associated periodontal disease remain the most common chronic diseases in current society. In the future, individually tailored, more effective therapeutic treatment options could be provided through the application of tissue engineering and regenerative medicine and dentistry (TERMD) approaches. A relevant finding is the potential of both dental mesenchymal and dental epithelial cells to regenerate mineralized dentin and enamel tissues, respectively. Materials and Methods: In the current study, a multi-layered, bioengineered tooth bud model was assembled by combining human dental mesenchymal (hDM) and porcine dental epithelial cells (pDE). The hDM cells were seeded onto poly(epsilon-caprolactone)/ poly (lactide-co-glycolide) (PCL/PLGA) wet electro-spun scaffolds overlayed with confluent pDE cell sheet harvested from thermo-reversible tissue culture plates. The so-formed multi-layered bioengineered tooth bud was then used to study the mineralization potential of the dental cells in in vitro culture. It was hypothesized that the addition of the in media soluble factors Insulin-like growth factor 1 (IGF-I) and the extracellular matrix derivate Emdogain (EMD) would result in enhanced differentiation and mineralized dental tissue formation. Scanning Electron morphological observation was used to characterize scaffolds porosity. Histological and immunofluorescent analyses confirmed the localization of hDM cells inside the scaffold, an intact pDE cell sheet, and the presence of beta-integrin 1-positive cell-cell junctions connecting the two. Results: Scanning Electron Microscopy showed that EMD, in particular, enhanced the mineralization potential of pDE cells. qRT-PCR analyses showed that both EMD and IGF-1 significantly enhanced the expression of Ameloblastin (AMBN), reflecting pDE cell differentiation. Conclusion: In conclusion, these results proved the hypothesis that both EMD and IGF-1 should be considered for their utility in preclinical dental tissue engineering approaches.